Peran Bhabinkamtibmas Dalam Mencegah Penyebaran Paham Radikal - Satya Kurnia (Police Studies Review, 2020)
The multiplicity of Indonesia, especially about Islam Religion generate radical thinking. Then, the doers spread out those radical thinking. Tasikmalaya is a prone district where radical thinking usually spread. Therefore, Polres Tasikmalaya need to prevent radical thinking spreadness through Bhabinkamtibmas. But in reality, there is still some member of Bhabinkamtibmas who did not executed their duties well. The write of this thesis used qualitative research approach and the methods of analytical and descriptive research. This thesis main focuses are radical thinking/radicalism, Bhabinkamtibmas, and Polres Tasikmalaya. The source of this thesis was obtained from an interview with Kapolres, Kasat Binmas, Kasat Intel, Bhabinkamtibmas Polres Tasikmalaya and some relevant institution in Tasikmalaya, also Polres Tasikmalaya’s data or documents. The data was collected by an interview technique, observation and document analysis. Validation data technique used source, method, and teory triangulation. Technique used to analyze data in this thesis are data presentation technique, data reduction and by drawing a conclusion. The result of these researches show the causes of radical thingking or radicalism in Tasikmalaya is because there are still an education that is only focused on Islam religion, a few of kids whose still search for identity without the roles of parents to learn, low economic status and the denied of some people with high knowledge in Islam Religion there. Moreover, there is still Bhabinkamtibmas Polres Tasikmalaya who is not execute their duties well because the lack of organizational planning, implementation of an action and lack of duties control in Bhabinkamtibmas Polres Tasikmalaya. The suggest from this thesis is Polres Tasikmalaya need to increase the number of their personnel whose competent in Islam Religion and Nationality Education also have an comprehensive insight about their fostered village, Bhabinkamtibmas should be more active on participate in their fostered village’s religion activites and Bhabinkamtibmas need to collaborate with another relevant institutions to make every plan solved right on target in their fostered village. Therefore, Bhabinkamtibmas could give a good influence to their fostered village.